1998
DOI: 10.1046/j.1365-2168.1998.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of electrolysis-induced hepatic necrosis

Abstract: Predictable and reproducible areas of liver necrosis are produced with electrolysis. If these results extrapolate to larger animal models, this technique has potential for patients with irresectable primary and secondary liver tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
2
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 28 publications
3
60
2
1
Order By: Relevance
“…Direct current is passed along electrode catheters which have exposed platinum electrodes. The catheters are inserted directly into the tumour under intra-operative ultrasound control and the duration of treatment calculated from a dose-response curve from previous animal experiments [12, 13]. Tissue necrosis is caused by the production of chlorine gas and hydrogen ions at the anode and hydrogen gas and sodium hydroxide at the cathode [14]thereby creating a pH gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Direct current is passed along electrode catheters which have exposed platinum electrodes. The catheters are inserted directly into the tumour under intra-operative ultrasound control and the duration of treatment calculated from a dose-response curve from previous animal experiments [12, 13]. Tissue necrosis is caused by the production of chlorine gas and hydrogen ions at the anode and hydrogen gas and sodium hydroxide at the cathode [14]thereby creating a pH gradient.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study in the normal rat liver [29], it tumour cells were cultured on microspheres and injected into the portal vein. This technique resulted in the growth was shown that in the majority of cases, the 'primary' electrolytic hepatic lesion was associated with a 'secondof multiple, discrete liver tumours.…”
Section: Discussionmentioning
confidence: 99%
“…In each rat only one tumour normal rat liver ( fig. 2) [29] by examining various comwas treated; the untreated tumour acted as the animal's binations of coulombs and milliamps and the resulting own control. Two weeks after tumour implantation and lesion size in the rat liver.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 24 hours after the application showed a significant increase in serum aspartate aminotransferase and alanine aminotransferase, both markers of cell damage. (17) It believed that Achilles tendinopathy pain is related to a process of degeneration of the tissue, to be reduced or ceased as tissue repair. Tissue repair is a dynamic state comprising different processes, including inflammation, cell proliferation and synthesis of the elements that constitute the extracellular matrix, such as collagen, elastin, and reticulin.…”
Section: Application Of Percutaneous Microeletrólisis (Mep®)mentioning
confidence: 99%